50th years of research on doping prevention. A narrative review of tracks and perspectives - Lucidi, F.; Chirico, A. (International Journal of Sport Psychology, 2020)
While the use of Performance-Enhancing and Aesthetic Substances (PAES) has been observed for thousands of years, doping has been conceptualized and regulated only in the modern era. The aim of the present study was to review the doping prevention theme in a narrative manner. The theoretical and research considerations presented in this article overall are guided by the assumption that doping behavior partly depends on the dynamic interplay between a set of individual factors, its environment, and the goal that guide the intentional behavior. Relatedly, this article introduces the general hypothesis that these forms interplay between socio-cognitive variables of particular importance in contributing to the scientific understanding of doping use, as they might help accounting for individual differences in doping intentions and doping use. In doing so, there are described theoretical and research frameworks that indirectly support this general view, and subsequently, is addressed the value of a focus on doping research. Finally, there are reported different research programs that have been tried to find empirical support to the hypothesized linkages between intervention, their efficacy and doping use in various sport contexts.